Triple modality testing by endoscopic retrograde cholangiopancreatography for the diagnosis of cholangiocarcinoma - Arjun Nanda; Jason M. Brown; Stephen H. Berger; Melinda M. Lewis; Emily G. Barr Fritcher; Gregory J. Gores; Steven A. Keilin; Kevin E. Woods; Qiang Cai; Field F. Willingham (Therapeutic Advances in Gastroenterology, 2015)
Objectives: Brush cytology has a low sensitivity for the diagnosis of cholangiocarcinoma. This study aimed to compare the standard approach (brush cytology) with a triple modality approach utilizing brush cytology, forceps biopsy and fluorescence in situ hybridization in terms of sensitivity and specificity for the diagnosis of cholangiocarcinoma. Methods: In a retrospective study at a single academic center, 50 patients underwent triple modality testing. Additionally, 61 patients underwent brush cytology alone. Intervention was endoscopic retrograde cholangiopancreatography with brush cytology, fluorescence in situ hybridization, and forceps biopsy. The main outcome measures included sensitivity, specificity, positive predictive value and negative predictive value. Results: Overall, 50 patients underwent triple tissue sampling, and 61 patients underwent brush cytology alone. Twenty-two patients were eventually diagnosed with cholangiocarcinoma. Brush cytology had a sensitivity of 42%, specificity of 100%, positive predictive value of 100% and negative predictive value of 88%. Triple tissue sampling had an overall sensitivity of 82%, specificity of 100%, positive predictive value of 100%, and negative predictive value of 87%. Within the triple test group, brush cytology had a sensitivity of 27%, forceps biopsy had a sensitivity of 50%, and fluorescence in situ hybridization analysis had a sensitivity of 59%. Conclusions: A triple modality approach results in a marked increase in sensitivity for the diagnosis of cholangiocarcinoma compared with single modality testing such as brush cytology and should be considered in the evaluation of indeterminate or suspicious biliary strictures.